PENGARUH PEMBERIAN EKSTRAK DAUN KELOR (Moringa oleifera Lamk) TERHADAP KUALITAS MIKROBIOLOGI DAN ORGANOLEPTIK DAGING SAPI - Beti, Venansia Nona; Wuri, Diana Agustiani; Kallau, Novalino H. G. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2020)
Beef is one type of meat that is quite popular with almost all Indonesian people, especially in East Nusa Tenggara (NTT). Storage of beef at room temperature and open space can accelerate the occurrence of decay in meat. This is because the complete nutritional content and high water content in meat can be a good medium for the growth of pathogenic bacteria or spoilage bacteria. One of the efforts that can be done to prevent meat rot is to do a natural preservative method by utilizing plant parts that contain antimicrobial compounds. Moringa leaves are one part of the plant which is known to have antimicrobial compounds. This study aims to determine the effect of Moringa oleifera Lamk leaf extract on the microbiological and organoleptic quality of beef. This research is an experimental laboratory research. A total of 48 thigh beef (Biceps femoris) beef samples were tested in this study using a completely randomized factorial pattern design, namely concentration factors of 0% (K0), 5% (K1), 10% (K2), and 15% (K3) extract Moringa leaf and long storage factor at room temperature are 0 hours, 6 hours, 12 hours, and 18 hours and repeated three times. The parameters tested were color quality, texture, aroma, initial decay test, pH test, and total plate count (TPC) test. The results showed changes in the color, aroma, and texture of the meat. The Eber test shows the K3 group can last up to 18 hours. There was a very significant difference between the concentration of Moringa leaf extract on the length of storage of meat and the pH value of meat (P<0,01). Moringa leaf extract concentration factors and meat storage duration significantly influence the TPC value (P<0,01). The TPC value in the K3 group is below the SNI contamination limit for storage room temperature less than 18 hours.